Mothers and Premature Infants’ Emotional Interactions in a Neonatal Infant Care Unit: Case Studies - Tropiano, Ligia M.C.C.; Fiamenghi-Jr, Geraldo A.; Blascovi-Assis, Silvana M. (European Scientific Journal, ESJ, 2017)
The aim of this study was to describe the ways premature infants and their mothers emotionally interact in the first weeks of their lives. In order to understand the intersubjective dyadic interaction between mother and premature infant, a qualitative and descriptive approach to research has been adopted. Four dyads comprised of primiparae women and their newly-born premature infants took part in the study. The babies were born prematurely after 28 to 35 weeks of gestation and admitted to the neonatal intensive care unit (NICU). Data was collected filming the first dyadic interaction with infant in the mother’s arms, lasting between 15 to 30 minutes. After that first registry, dyadic behaviors between mother and baby were described and categorized following the intersubjective categories suggested by Fiamenghi (1999) and Fiamenghi et al. (2010). Results showed that dyads display positive emotions, with infants’ behaviors falling into the categories of negotiation, interaction and emotional curiosity; as well as a low frequency of negative behaviors. The outcome of this research reinforces the need to adopt a humanizing approach to prematurely born infants and their mothers in NICU, as well as training and awareness of the whole multidisciplinary team that deals with them.